2018
DOI: 10.1111/cid.12622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dental implant stability in bone phantoms: Comparison between a quantitative ultrasound technique and resonance frequency analysis

Abstract: The results show that ultrasound technique provides a better estimation of different parameters related to the implant stability compared to the RFA technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
2
34
0
1
Order By: Relevance
“…However, no clinical validation of any of these two methods was provided in this article. Analogously, Vayron et al [ 72 ] found a significant correlation between ISQ measured by the Osstell device and marginal bone loss, as well as Miyamoto et al, who gave strong evidence of a linear relationship between ISQ values and cortical bone thickness [ 73 ]. Finally, Farré-Pagès et al reported a statistically significant relationship between different bone qualities, according to Lekholm and Zarb’s classification [ 74 ] and ISQ values [ 75 ].…”
Section: Clinical Validationsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, no clinical validation of any of these two methods was provided in this article. Analogously, Vayron et al [ 72 ] found a significant correlation between ISQ measured by the Osstell device and marginal bone loss, as well as Miyamoto et al, who gave strong evidence of a linear relationship between ISQ values and cortical bone thickness [ 73 ]. Finally, Farré-Pagès et al reported a statistically significant relationship between different bone qualities, according to Lekholm and Zarb’s classification [ 74 ] and ISQ values [ 75 ].…”
Section: Clinical Validationsmentioning
confidence: 91%
“…The authors explain this result considering that ISQ is related to the vibration of the whole bone–implant system, while the QUS response was related to bone properties on a confined volume that was about 30 µm around the implant [ 80 ]. Another study compared the results obtained with these two technologies in dental implants placed in bone-mimicking phantoms: again, QUS resulted to be a more accurate tool, with higher sensitivity, especially with reference to the final drill diameter [ 72 ]. Nonetheless, the reliability of the QUS technique still needs to be evaluated in clinical studies.…”
Section: Clinical Validationsmentioning
confidence: 99%
“…where A is an arbitrary constant and f c is its central frequency, which was set to 10 MHz throughout the study as it corresponds to the value used in the QUS device developed by our group (Mathieu et al, 2011b;Vayron et al, 2013;Vayron et al, 2014a;Vayron et al, 2014c;Vayron et al, 2018a;Vayron et al, 2018b). Moreover, the results obtained in Heriveaux et al (2018) indicate that using a frequency equal to 10 MHz guarantees an acceptable sensitivity of the ultrasound response on changes of the biomechanical properties of the BII (a resolution of around 2-12 lm depending on the implant roughness was obtained).…”
Section: A Description Of the Numerical Modelmentioning
confidence: 99%
“…A preclinical validation of the device in rabbits was carried out [ 31 ], and showed that the measurement was significantly sensitive to healing time. More recently, the results that were obtained with RFA and QUS techniques were compared using implants that were inserted in bone mimicking phantoms [ 32 ]. Different values of trabecular bone density and cortical thickness were considered to assess the effect of bone quality on the respective indicators (UI and ISQ) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%